2022
DOI: 10.1063/5.0124291
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional direction-of-arrival estimation based on time-domain-coding digital metasurface

Abstract: Direction-of-arrival (DOA) estimation is one of the most critical technologies of radar, remote sensing, and wireless communications. The traditional DOA estimation is closely related to phased array antennas, which require complicated and expensive hardware and high-power consumption. Metasurface can manipulate electromagnetic waves without using massive transceivers, which makes it possible to realize antenna arrays in a cost-effective way. Here, we propose a strategy of DOA estimations by using a time-domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the past years, the metasurfaces have been used in the applications of beam steering [21][22][23], holography [24][25][26], wavefront manipulation [27,28], polarization converter [29,30] and lens [26,[31][32][33]. It is also indicated that electromagnetic waves can be manipulated with metasurfaces by modulating the phases in the space as well as the time domains [34][35][36][37][38][39][40][41][42]. This provides more degrees of freedom for dynamically controlling the reflection from an object [38,42].…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, the metasurfaces have been used in the applications of beam steering [21][22][23], holography [24][25][26], wavefront manipulation [27,28], polarization converter [29,30] and lens [26,[31][32][33]. It is also indicated that electromagnetic waves can be manipulated with metasurfaces by modulating the phases in the space as well as the time domains [34][35][36][37][38][39][40][41][42]. This provides more degrees of freedom for dynamically controlling the reflection from an object [38,42].…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Recent approaches explore a diverse range of strategies, from using metasurfaces as an additional layer alongside antenna arrays to minimize computational requirements by performing 2D discrete Fourier transformations, [24] to substitute traditional antenna arrays with a single programmable metasurface associated with a single receiver. [25,26] These approaches introduce spatiotemporal modulation methods [27,28] and machine learning [29] to further reduce material and computational complexity. Although these methods have led to significant advances, challenges such as data quantity and processing time persist, necessitating ongoing exploration and innovation in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Hence it is necessary to integrate the positioning function on PMS. For instance, introduced the compressive sensing to achieve the direction of arrival (DoA) estimation based on a single channel PMS 40,45 ; combined the space-time-coding (STC) technique to estimate multiple targets 46,47 , etc. But they are half duplex, and cannot estimate the distance of targets.…”
Section: Introductionmentioning
confidence: 99%